The Substitution of Natural Gas with Biomethane in an Industrial Fluidized Bed Sand Drying Process - Santos Machado, Mônica Valéria dos [UNESP]; de Carvalho, João Andrade [UNESP]; Ávila, Ivonete [UNESP]; Nascimento, Andreas; Solferini de Carvalho, Felipe (MDPI, 2025)
Drying sand using a fluidized bed process is very common in the industries that use the material in their processes. The fluidized bed system works by introducing gas and excess air into a bed to achieve the temperature required to dry the particulate material. This system is used in various industrial processes, including gasification, pyrolysis, grain drying and industrial sand. The main objective of this research was to analyze the sand drying system used in an industrial process with a fluidized bed and to verify the interchangeability and costs between natural gas and biomethane operation. To achieve this, an energy balance was developed using a specific mathematical model to calculate the amount of fuel required for the process as a function of the excess air. The specific consumption of fuel gas (m3 of gas per t of dry sand) is the most important parameter for the performance of the sand drying equipment, and the mathematical model developed in this research was used to determine this parameter. It was found that the specific consumption drops significantly until the flue gas temperature reaches around 600 °C. Beyond this point, it continues to decrease, but at a much slower rate. To determine the energy balance, this study was divided into two parts: the combustion chamber and the fluidizer itself. In the combustion chamber, the temperature of the injected gases was determined as a parameter, and sand with a known initial moisture content was considered in the fluidizer. In comparison with real industrial data collected from a company consuming natural gas, the model achieved good agreement. In terms of interchangeability between operations with natural gas and biomethane, the results show that the gases are interchangeable in sand drying, although there is a difference between the Wobbe indices of more than the usually recommended 5%.
Keywords: biomethane; fluidized bed equipment; sand drying